2014
DOI: 10.1016/j.neo.2014.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Glioma Formation: Iterative Perivascular Glioma Growth and Invasion Leads to Tumor Progression, VEGF-Independent Vascularization, and Resistance to Antiangiogenic Therapy

Abstract: As glioma cells infiltrate the brain they become associated with various microanatomic brain structures such as blood vessels, white matter tracts, and brain parenchyma. How these distinct invasion patterns coordinate tumor growth and influence clinical outcomes remain poorly understood. We have investigated how perivascular growth affects glioma growth patterning and response to antiangiogenic therapy within the highly vascularized brain. Orthotopically implanted rodent and human glioma cells are shown to com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
125
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 139 publications
(139 citation statements)
references
References 51 publications
13
125
0
1
Order By: Relevance
“…A previous study from our lab showed that antibodies successfully cross the blood-brain barrier (BBB) and penetrate into the TME; the loss of BBB integrity associated with GBM growth may further support this process. [59][60][61][62][63] A preliminary analysis of Gr-1 antibody-treated mice showed that the efficacy of depletion lasted for approximately 4 days. Therefore, to ensure the maintenance of TK/Flt3L-induced tumor-specific T cell proliferation, we administered the antibody so that MDSCs would be eliminated from the GBM TME around the peak of the T cell response, which occurs 7 days after the administration of gene therapy.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study from our lab showed that antibodies successfully cross the blood-brain barrier (BBB) and penetrate into the TME; the loss of BBB integrity associated with GBM growth may further support this process. [59][60][61][62][63] A preliminary analysis of Gr-1 antibody-treated mice showed that the efficacy of depletion lasted for approximately 4 days. Therefore, to ensure the maintenance of TK/Flt3L-induced tumor-specific T cell proliferation, we administered the antibody so that MDSCs would be eliminated from the GBM TME around the peak of the T cell response, which occurs 7 days after the administration of gene therapy.…”
Section: Discussionmentioning
confidence: 99%
“…GA was also preferred for grade 4 gliomas, which more often present perivascularly and with adhesions to the M2 and M3 branches of the middle cerebral artery [21]. Pressure on these branches is painful for AC patients, so GA is typically used for grade 4 gliomas.…”
Section: Choice Of Anesthesia Techniquementioning
confidence: 99%
“…Growing evidence indicates that nuclear accumulation of HIF results in transcriptional activation of the vascular endothelial growth factor (VEGF) whose pathway is modulated by reactive oxygen species (ROS), and demonstrating VEGF downregulation following HIF1a gene deletion and that HIF1/2 determined VEGF levels [4,28,44]. Francescone et al identified that YKL-40 (CHI3L1) closely upregulates VEGF expression, and YKL-40-induced tumor vasculogenesis is at least partially dependent on VEGF [21].…”
Section: Glioblastoma Stem Cells and Ykl-40mentioning
confidence: 99%
“…Baker et al [4] studied the requirement for neoangiogenesis in perivascular glioma by treating animals with angiogenesis inhibitors bevacizumab and DC101. In their work, the authors explained that perivascular invasion give rise to neoangiogenesis by digesting normal brain tissue in a VEGF-independent way that leads to tumor invasion.…”
Section: The Role Of Ykl-40 Glial Cells and Perivascular Scaffold Inmentioning
confidence: 99%